Hvordan etablere en sunn livsstil hos en overvektig inaktiv kvinne med psykisk utviklingshemning - Christine Tørris; Mette Kristin Rach; Line Margrethe Solhaug (Septentrio Academic Publishing, 2015)
How to establish a healthy lifestyle in an overweight, inactive woman with an intellectual disability Overweight and obesity are associated with increased health risks and shortened life span. The prevalence of overweight and obesity is increasing, and a higher prevalence of obesity has been observed in persons with intellectual disability than in the general population. In this study, we want to establish a healthy lifestyle with a healthy diet and increased physical activity in an obese, inactive women with intellectual disability. Using interventions based on applied behavioural analysis, the women have established new habits in terms of diet and increased physical activity. The number of hours with physical activity per week has doubled, and both weight and waist circumference decreased during the eight weeks of the study. She maintained her new healthy lifestyle, after the study. More research is needed in interventions that can help reduce obesity in persons with intellectual disability.